Kepuasan Kerja : Satu Kajian di Sekolah-Sekolah Menengah Teknik Zon Utara - Zulkifli, Md. Razali (2002)

(untitled)
The purpose of this research is to study the job satisfaction level and the factors that influence their satisfaction for the Technical School teachers. The factors studied are job situation, pay, promotions, supervision, peers and overall job situation. The research was done ini order to determine the relationship between the factors involved. The research involves 120 respondents among teachers from three Technical School Northern Zone to examine their job satisfaction. The Likert five points scale is used to get the teachers response. The questions asked are based on the six factors studied. The data obtained is analysed using the descriptive statistical method to determine the frequency, percentage, mean and standard deviation. The inference statistical method which includes t-test and ANOVA. The finding of this study shows that there are no significant differences factor of job satisfaction with factor of demographic. This research are importance to school and education department in studying the significant relationship of work behavior and job satisfaction of teacher.